The Role of CD40 in Allergic Rhinitis and Airway Remodelling - Ke-Jia Cheng; Min-Li Zhou; Yong-Cai Liu; Chen Wang; Ying-Ying Xu (Mediators of Inflammation)
Background. Allergic rhinitis (AR) affects millions of people and is lack of effective treatment. CD40 is an important costimulatory molecule in immunity. However, few studies have focused on the role of CD40 in AR. Methods. In this study, we built mouse model of chronic AR. The mice were divided into the AR, control, intravenous CD40 siRNA, and nasal CD40 siRNA groups (n=6 each). We detected OVA-sIgE, IL-4, IL-5, IL-13, IL-10, IFN-γ, and TGF-β levels in serum and supernatant by ELISA, CD40+ splenic DCs, and Foxp3+ Tregs by flow cytometry and CD40 mRNA by RT2-PCR. We also used PAS and MT stains to assess tissue remodelling. Results. (1) The OVA-sIgE, IL-4, IL-5, and IL-13 levels in the serum or supernatant of nasal septal membrane of AR mice were significantly higher than control. After treated with CD40 siRNA, those indicators were significantly decreased. The IFN-γ, IL-10, and TGF-β levels in AR mice were significantly lower than that in control and were increased by administration of CD40 siRNA. (2) AR mice had significantly fewer Foxp3+ Tregs in the spleen than control mice. After treated with CD40 siRNA, AR mice had significantly more Foxp3+ Tregs. (3) AR mice exhibited a significantly higher CD40 mRNA levels than control. Administration of CD40 siRNA significantly reduced the CD40 mRNA level. (4) The AR mice showed significantly greater collagen deposition than the control in MT staining. Applications of CD40 siRNA significantly reduced the collagen deposition in AR mice. Conclusion. CD40 siRNA therapy shows promise for chronic AR as it significantly attenuated allergic symptoms and Th2-related inflammation and upregulated Foxp3+ Tregs. CD40 plays a role in tissue remodelling in AR, which can be inhibited by CD40 siRNA application.